REFLEXOS INDIVIDUAIS DO USO PESSOAL E EXCESSIVO DE COMUNICADORES INSTANTÂNEOS NO AMBIENTE DE TRABALHO - MUNIZ, LEONARDO MAIRENE (2015)
The internet is part of every people daily life and becomes increasingly accessible through different types of devices. Several studies have been conducted in order to assess the consequences of their excessive use in personal, academic and professional life. This paper aimed to identify if the concentration and social isolation are some of the reflections by the excessive use of instant messaging applications in the workplace. Some of the variables that assess aspects of excessive use of instant messaging are diminished impulse control, loneliness, social comfort, and digital distraction. Through a quantitative research approach, it was used scales applied to a sample of 283 people, the data was analyzed by multivariate techniques like Exploratory Factor Analysis and Multiple Linear Regression. The results of this study confirm that the excessive use of instant messaging is positive related to loss of concentration and the variable digital distraction exerts a greater influence than the diminished impulse control. However, according to the results, loneliness and social comfort cannot be said that there is a relationship in increasing social isolation due to lack of significance of the relationship.